2000
DOI: 10.1037/0021-9010.85.3.439
|View full text |Cite
|
Sign up to set email alerts
|

An examination of organizational and team commitment in a self-directed team environment.

Abstract: A model hypothesizing differential relationships among predictor variables and individual commitment to the organization and work team was tested. Data from 485 members of sewing teams supported the existence of differential relationships between predictors and organizational and team commitment. In particular, intersender conflict and satisfaction with coworkers were more strongly related to team commitment than to organizational commitment. Resource-related conflict and satisfaction with supervision were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
176
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(191 citation statements)
references
References 60 publications
1
176
0
10
Order By: Relevance
“…Second, we suggest that job interdependence encourages the expression of interdependent self-construals at work and helps people with higher interdependent self-construals to engage in work unit-oriented proactive behavior. Job interdependence refers to the extent to which employees must depend on others' work and interact with others to complete their jobs (Bishop & Scott, 2000;Kiggundu, 1983). High job interdependence provides strong signals to employees that they should be aware of both colleagues at work and their own contributions to the group (Morris & Steers, 1980).…”
Section: Interaction Effect Of Self-construal and Work Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we suggest that job interdependence encourages the expression of interdependent self-construals at work and helps people with higher interdependent self-construals to engage in work unit-oriented proactive behavior. Job interdependence refers to the extent to which employees must depend on others' work and interact with others to complete their jobs (Bishop & Scott, 2000;Kiggundu, 1983). High job interdependence provides strong signals to employees that they should be aware of both colleagues at work and their own contributions to the group (Morris & Steers, 1980).…”
Section: Interaction Effect Of Self-construal and Work Characteristicsmentioning
confidence: 99%
“…Furthermore, it is likely to be critical for those high in independent self-construals to shape their work tasks for their career development. We used three items assessing job interdependence from Bishop and Scott (2000). The response scale ranged from 1 ("strongly disagree") to 5 ("strongly agree").…”
Section: Work Characteristics We Used Three Items Assessing Job Automentioning
confidence: 99%
“…eficial to obtain knowledge of how people feel and react to their work and the relationship of various feelings and perceptions (Spector 1994 in Bishop andScott 2000). It is also clearly stated that the reason for using the self-reporting method is crucial to the purpose of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, previous findings (e.g. Beck and Wilson, 2000;Bishop and Scott, 2000;Rafferty and Griffin, 2009;Sagie,1998) have also shown that organisations benefit from a workforce that has a high level of job satisfaction and organisational commitment as the employees tend to be absent less, make positive contributions and stay with the organisation. Thus, an understanding of the relationship between work group identification and, job satisfaction and organisational commitment is desirable.…”
Section: Overview Of Research About Work Group Identification and Hypmentioning
confidence: 98%